2023
DOI: 10.3390/ijms24108861
|View full text |Cite
|
Sign up to set email alerts
|

Microphthalmia-Associated Transcription Factor: A Differentiation Marker in Uveal Melanoma

Abstract: Microphthalmia-associated transcription factor (MITF) is an important regulator of melanogenesis and melanocyte development. In cutaneous melanoma, MITF loss has been linked to an increased expression of stem cell markers, a shift in epithelial-to-mesenchymal transition (EMT)-related factors, and increased inflammation. We explored the role of MITF in Uveal Melanoma (UM) using a cohort of 64 patients enucleated at the Leiden University Medical Center. We analysed the relation between MITF expression and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…MITF was suggested to have a dual role in benign and malignant melanocytic cells since it was proposed to promote local proliferation, while loss of MITF expression could increase invasion [ 97 , 98 ]. Gelmi et al [ 99 ] recently demonstrated that low MITF expression was associated with inflammatory markers and epithelial-mesenchymal transition. They proposed that MITF loss in UM could be related to de-differentiation to a less favorable epithelial-mesenchymal transition profile [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MITF was suggested to have a dual role in benign and malignant melanocytic cells since it was proposed to promote local proliferation, while loss of MITF expression could increase invasion [ 97 , 98 ]. Gelmi et al [ 99 ] recently demonstrated that low MITF expression was associated with inflammatory markers and epithelial-mesenchymal transition. They proposed that MITF loss in UM could be related to de-differentiation to a less favorable epithelial-mesenchymal transition profile [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gelmi et al [ 99 ] recently demonstrated that low MITF expression was associated with inflammatory markers and epithelial-mesenchymal transition. They proposed that MITF loss in UM could be related to de-differentiation to a less favorable epithelial-mesenchymal transition profile [ 99 ]. Borgdorff et al [ 100 ] found that AMPK was an important regulator for the maintenance of MITF protein levels in melanocytic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation